Internalization of Imam Zarkasyi's Educational Values in the Spiritual Program: Character Strengthening Strategies at SMAN 1 Makarti Jaya - Koswara, Ari; Asmaisyah, Asmaisyah; Fauzi, Muhammad; Mansur, Abu (Universitas Pahlawan Tuanku Tambusai, 2026)
Strengthening students’ character has become a major priority in modern education, requiring relevant and applicable value internalization models. This study is motivated by the limitations of previous research that tends to address character education in a general manner and the lack of studies integrating Imam Zarkasyi’s educational values within public senior high school contexts. This research aims to describe the forms of value internalization, analyze the implementation of spiritual programs, and evaluate the effectiveness of strategies applied at SMAN 1 Makarti Jaya. The study employs a qualitative approach with a case study design. Research informants include the principal, spiritual program supervisors, Islamic education teachers, and students. Data were collected through in-depth interviews, observations, and document analysis, and were analyzed using data reduction, data display, and conclusion drawing techniques based on the Miles and Huberman model. The findings reveal that the internalization of Imam Zarkasyi’s values is realized through structured religious habituation, teachers’ exemplary behavior as role models, and the strengthening of a school culture grounded in discipline and responsibility. These strategies have proven effective in enhancing students’ religiosity, integrity, and discipline, while also reinforcing a value-based and character-oriented school ecosystem.